IMPACT OF TILLAGE SYSTEMS ON RAINFALL WATER RUNOFF IN THE DOKA WATERSHED, GADARIF, SUDAN - Shaker , Babiker Ahmed; Alhamem , Redwan Musaad Modawi; Saeed , Amir Bakheit (Research Journal of Agriculture (RJA), 2024)
A field experiment was carried out during the growing seasons 2017/18 and 2018/19 under rainfed conditions to study the impact of some tillage systems on rainfall water runoff in the Doka Watershed, Gadarif State, Sudan. The 100 feddan experimental site was located at a latitude of 12° 45´ N, longitude of 35° 15´ E, and elevation of 540 m above mean sea level. Three water harvesting treatment systems were implemented: contour tillage (CT) (chisel plow + earth contour embankments), zero tillage (ZT) (conservation tillage), and the traditional farmer’s practice using the wide level disc (WLD) plow which was taken as the control. The experiment was conducted in a Randomized Complete Block Experimental Design (RCBD) with three replications. The sorghum (Sorghum bicolor) Wad Ahmed variety was used as an indicator plant. The statistical analysis software MSTAT was used to analyze the data. The results show that contour tillage produces the lowest amount of surface runoff compared to the control. There was positive correlation between the rainfall characteristic and the volume of surface runoff. It is evident that contour tillage had a noticeable positive impact on the management practices of vertisol by reducing surface runoff